ANALISIS IMPLEMENTASI APARAT PENEGAK HUKUM POLSEK GROGOL PETAMBURAN DALAM PASAL 27 AYAT 2 UU ITE - Putra, M.Adi Pratama (Universitas Sultan Ageng Tirtayasa, 2023)
Online gambling is one of the negative impacts of technological development in the digital era, which utilises the internet for illegal activities. This phenomenon causes bad effects, both individually, such as financial loss and addiction, as well as socially, such as criminality and social relationship rift. Article 27 Paragraph 2 of the ITE Law prohibits the distribution, transmission, and access to electronic information that is loaded with gambling. This research aims to analyse the implementation of the article by the Grogol Petamburan Police in eradicating online gambling in West Jakarta. The method used is qualitative with a descriptive approach. Data is obtained through interviews, observations, and document analysis, then analysed using Miles & Huberman techniques which include data reduction, data presentation, and drawing conclusions. Data validity is maintained by technical triangulation. The research results show the efforts of the Grogol Petamburan Police in cyber surveillance, legal socialisation, and enforcement of online gamblers. However, challenges such as limited technological resources, low public legal awareness, and the complexity of gambling networks are still obstacles. Research recommends an increase in collaboration between law enforcement officers, the government, and the community to effectively overcome the problem of online gambling.